THE INFLUENCE OF COMPETENCE ON LOCAL GOVERNMENT FINANCIAL REPORT QUALITY WITH AUDIT QUALITY AS MEDIATING VARIABLE (Survey on the Inspectorate of East Java Province) - MOCHAMMAD RASYID POEDJIJANTO, 041311333285 (2017)
Financial report quality of the government is an important factor that needed to be concerned, with the competence of inspectorate auditor, the audit quality can improve the financial report quality. This research aimed to obtain the evidence of and interaction between the competence and the audit quality, the competence and financial report quality, the audit quality and financial report quality, and the competence and the financial report quality with audit quality as an mediation. This research is a correlation research. The research population is the auditor of Inspectorate in Province of East Java. This research uses convenience sampling. Data was collected by giving questionnaire to all respondents. Data is analyzed with SEM regression method by SmartPLS 2.0. The result shows that the competence has positive significant effect to the audit quality, the competence has positive not significant to the financial report quality, the audit quality has positive significant to the financial report and the competence has positive significant to the financial report quality with audit quality as mediating.